Analysis and investigation of the failure elevator induced by dual effects of cyclic alternating load and improper heat treatment. (November 2022) - Hou, Duo; Xiao, Zhongling; Zhang, Zhi; Deng, Hu; Lu, Qi
Highlights: The intact lower bainite structure of the lath orientation weakens the strength and toughness of the elevator. Insufficient tempering heat treatment aggravates the embrittlement of elevators containing structural defects and reduces the structural stability. The various alternating loads that the elevator bears during the service process cause dislocation slip in the part containing non-metallic D-type inclusions. The slope surface of the elevator produces obvious deformation streamlines and folds, resulting in strain hardening, increased brittleness and deformation accumulation, which induce crack nucleation and expansion. Under the action of impact and cyclic alternating load, the crack nucleates and propagates near the loose-leaf axis of the elevator, and finally the mixed crystal brittle fatigue fracture occurs. Abstract: Aiming at the deformation and fracture of slope elevator caused by the cyclic alternating load in service, analyzes and studies the failure reasons and mechanisms from microstructure, physical and chemical properties, and service state. The microstructure of the elevator was lower bainite that preserves the intact of the laths orientation, with high P element content, a certain amount of low harmful low-melting-point elements, and presence of D-type non-metallic inclusions, led to low impact toughness. It indicated that failure of the elevator can be attributed to dual effects of load and improper heat treatment, caused dislocation glide to occur in the crystals, eventually resulting in a mixed-crystal-type brittle fatigue fracture. It was advised to strictly control the content of trace elements, rationally optimize the heat treatment process, and select microstructure with good resistance to fatigue impact and alternating load, to improve the deformation resistance and critical fracture toughness of the elevator.